Total Quality Management in the stock exchange: A case study - Gurcharan, S.; Wong, E.S.K.; Fereidoon, Z. (Academic Journals, 2010)
The purpose of this study is to explore, assess, and identify the implementation patterns of Deming's principles in Malaysia's Kuala Lumpur Stock Exchange. By applying Deming's 14-point quality criteria to these service providers, Deming's significance factors are then ranked to explain the variation in the finance service providing companies sampled. The basis of this research is the degree of consensus between managers of diverse backgrounds using Deming's 14-point quality criteria using a middle management sample base. The main findings of the study are that although companies believe that TQM would have a positive impact on the quality of the final services and products, they did so with little enthusiasm. Results show that, the use of Total Quality Management (TQM) within the Malaysian financial industry to solve quality problems is increasing. The results also show that companies do include their major customers in their quality initiatives